2019
DOI: 10.5650/jos.ess19124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Compounds in <i>Coleus forskohlii</i> Extract Involved in the Induction of Hepatic CYP and Fatty Liver in Mice

Abstract: Introduction There has been a recent increase in the use of herbal dietary supplements 1 , as consumers perceive the term natural to indicate safety and herbal ingredients are believed to be effective due to their long use in complementary and alternative medicines. However, herbal ingredients are not subjected to routine safety examination, and recent studies have revealed that herbal products, especially those used for weight loss, can cause adverse events such as serious hepatic failure 2. In fact, hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…CYP gene expression is transcriptionally regulated by the pregnane X receptor (PXR) and the constitutive androstane receptor. It has been reported that mouse Cyp3a11 is a PXR-regulated gene, 36) and CFE induction of CYP has been shown to involve PXR. 23) Differences in the CFE dose required for CYP induction between the intestine and liver may be due to differences in transcriptional regulation of the CYP gene.…”
Section: Discussionmentioning
confidence: 99%
“…CYP gene expression is transcriptionally regulated by the pregnane X receptor (PXR) and the constitutive androstane receptor. It has been reported that mouse Cyp3a11 is a PXR-regulated gene, 36) and CFE induction of CYP has been shown to involve PXR. 23) Differences in the CFE dose required for CYP induction between the intestine and liver may be due to differences in transcriptional regulation of the CYP gene.…”
Section: Discussionmentioning
confidence: 99%